Positive psychology in cross-cultural narratives: Mexican students discover themselves while learning Chinese - Oxford, Rebecca L.; Cuéllar, Lourdes (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2014)
Using the principles of positive psychology and the tools of narrative research, this article focuses on the psychology of five language learners who crossed cultural and linguistic borders. All five were university students learning Chinese in Mexico, and two of them also studied Chinese in China. The grounded theory approach was used to analyze and interpret the students’ narratives. Seligman’s (2011) PERMA model, the centerpiece of the modern view of well-being, pro- vided the theoretical framework. The results led to the conclusion that language learning can be a major journey in selfdiscovery, rich in positive emotions tied to experiences of engagement, relationship, meaning, and accomplishment.
Keywords: language learner narrative; PERMA model; Chinese as a se- cond/foreign language